1991
DOI: 10.1016/0140-6736(91)92168-2
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocytes as initiators of inflammation

Abstract: Environmental stimuli responsible for inducing cutaneous inflammation include contact allergens and ultraviolet light. We postulate that these diverse stimuli trigger a cutaneous inflammatory response by directly inducing epidermal keratinocytes to elaborate specific pro-inflammatory cytokines and adhesion molecules. The consequences are activation of dermal microvascular endothelial cells and selective accumulation of specific mononuclear cells in the dermis and epidermis. Thus, keratinocytes may act as "sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
371
2
7

Year Published

1991
1991
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 707 publications
(396 citation statements)
references
References 25 publications
16
371
2
7
Order By: Relevance
“…To date, several cytokines, including IL-10t, TNF-c4 IL-6, IL-8, granulocyte-macrophage colony-stimulating factor (GM-CSF), and transforming growth factor-t~ (TGF-ct), have been found in epidermal keratinocytes [1]; however, only IL-lc~ could be shown to be stored in normal skin in a biologically active form [10]. Cytokines released from keratinocytes can be induced by environmental stimuli such as trauma, bacterial toxins and ultraviolet light.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several cytokines, including IL-10t, TNF-c4 IL-6, IL-8, granulocyte-macrophage colony-stimulating factor (GM-CSF), and transforming growth factor-t~ (TGF-ct), have been found in epidermal keratinocytes [1]; however, only IL-lc~ could be shown to be stored in normal skin in a biologically active form [10]. Cytokines released from keratinocytes can be induced by environmental stimuli such as trauma, bacterial toxins and ultraviolet light.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that various cytokines play important roles in homeostasis of normal skin and in its pathology [1]. Diverse stimuli trigger a cutaneous inflammatory response by activating specific pro-inflammatory cytokines, such as tumor necrosis factor-~ (TNF-c0 and interleukin-1 (IL-1); however, the detailed interrelation of the cytokines to the pathophysiological mechanism has not been well elucidated.…”
Section: Materials"mentioning
confidence: 99%
“…This may be because the threshold for irritancy of the hapten that is required to initiate the inflammatory response is much lower in vitro than in vivo. Haptens may act first on keratinocytes and then subsequent cytokine-induced responses will elicit the contact hypersensitivity (CHS) response (34). The cytokines involved may include TNFa and Il-1, as intradermal injections of these give a CHS-like response (33).…”
Section: Elicitation and Irritancymentioning
confidence: 99%
“…Nickel, for example, can cause nonspecific cytokine release from keratinocytes (34). Most contact allergens under patch test conditions have the capability of producing irritant reactions.…”
Section: Contact Allergens and Irritancymentioning
confidence: 99%
“…Resting KC synthesize and secrete low levels of cytokines, however, stimuli including allergens, irritants, ultraviolet light, bacterial products such as endotoxin, and physical trauma induce KC to produce significant amounts of cytokines. KC effectively function as basic signal transducers, capable of converting exogenous stimuli into host homeostatic responses [21]. LC also produce certain cytokines such as IL-1␤, IL-6, IL-12, and IL-18, which play important roles in initiation and modulation of cutaneous immune responses [22][23][24][25][26][27][28] (Table 1).…”
Section: Network Of Epidermal Cytokinesmentioning
confidence: 99%